DIALOG MONOTEISME TRINITARIAN DENGAN MONOTEISME TAUHID - Supriyanto Supriyanto (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2023)
Abstract.The Image of God in Trinitarian Monotheism Doctrine (Cjristian) and Tauhid Monotheism (Islam) show the uniquity and divers perspective in each religion. There is critiques to Trinitarian Monotheism from Islam scholars based on the concept of Tauhid Monotheism need a good attitude, openness from Christians to have dialogue with them so the doctrine could be explained, regarding that Christian also trust Monotheism. This Critique toward Monotheism Trinitarian will be based on the Islam Scholars (Abu Isa al-Warraq and Abd al-Jabbar), who are based their arguments upon Trinity in three big lines. The approach that will be served in this article is Asian perspective about Yin and Yang concept that can do clarity to understand Trinitarian Monotheism as inclusive, holistic, relational and dinamic. So, in the context of religious pluralities, dialogue is not only about social problems but also about deity, try to find mediation, paralel and vocal point in it.